Respectful Maternity Care: Evidences in Practice - Bista, Archana Pandey; Bista, Satkirti (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Worldwide, most of the women are still facing disrespect and abuse during labor and childbirth resulting in adverse health consequences. For addressing these issues, WHO has launched Respectful Maternity Care(RMC) as a universal right of every woman and newborn which needs to be ensured in all health Institutions. Thus, this review aimed to identify the types of abuse and disrespect woman are facing during intra partum period and to find out the practices related to RMC.Methods: Literature was searched from different sources like Google Scholar, CINAHL and Pub Med. Total 15 related original articles published from 2015 and onwards were included.Results: Among different form of abuse and disrespect, non-consented care, lack of autonomy, abandon and physical abuse were common respectively. RMC interventions have increased the awareness level among woman and health care providers and have been found effective to reduce psychological problems like depression, anxiety symptoms and increase wellbeing of woman and health of their newborns. Different factors like education, religion, environmental factors, and availability of resources influence RMC practices.Conclusions: Different form of abuse and disrespect are quite common during childbirth. For discouraging abuse and disrespect and to foster maternal and neonatal health RMC strategies need to be prioritized in all health care settings.